Ocular Histomorphometry of Free-Living Common Kestrels (Falco tinnunculus) - Werther, Karin [UNESP]; Candioto, Cinthia Graziela [UNESP]; Korbel, Rüdiger (Association of Avian Veterinarians (AAV), 2017)
We evaluated the histomorphometry of the eye structures (cornea, retina, choroid, and sclera) of 13 adult free-living common kestrels (Falco tinnunculus). Birds included in the study were euthanatized because of severe trauma from a motor vehicle injury. The eyes were enucleated immediately after euthanasia, fixed in 10% buffered formalin, and decalcified. The right eyes were cut vertically (dorsoventrally) and the left eyes cut horizontally (temporonasally). Tissues were processed, stained with hematoxylin and eosin, and evaluated by an image analysis software. The thicknesses of the diverse corneal layers were measured at 3 points; 2 at the peripheral region (A and C) and one at the central region (B). The thicknesses of the retina, choroid, and sclera were evaluated at 6 different positions. Measurements of the left and right eyes of the male and female birds were compared. The median thicknesses of the cornea at the peripheral points were 210.78 (A) and 197.79 (C) μm, and 129 μm at the central point (B). The thickness of the cornea did not differ significantly between males and females or between right or left eyes. The mean thicknesses of the retina, choroid, and sclera were 91.13, 20.74, and 92.8 μm, respectively. The thickness of the choroid and sclera did not differ significantly between the sexes or between the right and left eyeballs. The retinas of the females were significantly thicker than those of males at the points in the fundus of the eyeball, near the insertion of the pecten (optical nerves).
Keywords: avian; choroid; cornea; eye; Falco tinnunculus; histomorphometry; kestrel; retina; sclera; thickness